Dencik, L., Hintz, A., Redden, J. y Treré, E. (2022). Data justice - Calvo, Dafne (2023)
Advances in algorithmic systems and big data have redefined their relevance in contemporary social life. In response, the Data Justice Lab has developed a strong, multidisciplinary line of research to understand the context, identify challenges and propose solutions. Five years after its founding, the Lab's co-directors, Lina Dencik, Arne Hintz, Joanna Redden and Emiliano Treré, have published Data Justice, the first book in a thematic series for SAGE Publishing.